Readiness of F-16 Aircraft of the Indonesian Air Force in The Face of Regional Geopolitical Dynamics A Case Study of The Maintenance Depot 80 - Didid Hendro Sutrisno; Wibowo Wibowo; Tri Yuswo Ardi (Journal of Social Research, 2025)
The maintenance of F-16 fighter jets as strategic defense assets of the Indonesian Air Force (TNI AU) requires systems that adapt to technological advancements. Depot Maintenance 80 (Depohar 80), as the main heavy maintenance unit, faces the challenge of enhancing its capabilities through digital transformation in the era of Society 5.0. The main issue in this study is the suboptimal implementation of digital technology to support F-16 operational readiness. This research aims to analyze the mechanics’ competencies prior to digital transformation, identify the obstacles and challenges, and formulate strategies for digital maintenance implementation. A qualitative descriptive method was employed, utilizing literature review, interviews, and field observation. The findings reveal that human resource competencies in digital literacy need improvement, digital infrastructure is not yet fully established, and the integration of legacy systems with digital platforms still encounters technical challenges. It is concluded that digital transformation in Depohar 80 can significantly improve the operational readiness of F-16 aircraft, provided it is supported by intensive training, improved infrastructure, and gradual implementation of AI and IoT-based systems.